2017
DOI: 10.2106/jbjs.16.01247
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide Analysis of Femoral Neck Fractures in Elderly Patients

Abstract: This report identifies the changing trends in clinical practice in the treatment of geriatric femoral neck fractures in the U.S. Treating physicians should be aware of these trends, which include a decreasing national incidence of geriatric femoral neck fractures as well as an increase in the use of THA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
80
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(83 citation statements)
references
References 34 publications
3
80
0
Order By: Relevance
“…Femoral neck fracture is a representative trauma causing disability and morbidity, especially among elderly people. Open reduction and internal fixation often result in poor outcomes, and either hemiarthroplasty (HA) or total hip arthroplasty (THA) is recommended for displaced femoral neck fractures [ 1 , 2 ]. Previous studies have found that functionally demanding patients occasionally have problems after HA, such as pain, acetabular erosion, or implant loosening which, consequently, requires revision surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Femoral neck fracture is a representative trauma causing disability and morbidity, especially among elderly people. Open reduction and internal fixation often result in poor outcomes, and either hemiarthroplasty (HA) or total hip arthroplasty (THA) is recommended for displaced femoral neck fractures [ 1 , 2 ]. Previous studies have found that functionally demanding patients occasionally have problems after HA, such as pain, acetabular erosion, or implant loosening which, consequently, requires revision surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that THA requires a greater amount of blood transfusion than HA [ 1 , 6 , 8 , 15 ] and that it could be associated with a higher incidence of perioperative complications [ 16 , 17 ]. However, other studies reported no differences in the complication rate between the two procedures [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is not common in healthy individuals but common among athletes, military recruits, and young adults because of high energy activities such as sports and road traffic accidents, in adults because of falls, in women because of estrogen imbalances, and in patients because of bone mineralization and deficiencies [ [1] , [2] , [3] , [4] ]. In the USA in 2013, there were a reported 146 cases per 100,000 people [ 5 ]. Mortality can be as high as 30% in one year, particularly if treatment is delayed over 24 h [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Femur neck fractures are generally seen in patients with advanced age with co-morbidities which put them in high-risk category. [ 1 2 ] Anaesthesia maintenance in these patients depends on physical status, medications and co-morbidities and is generally maintained with general or neuraxial anaesthesia. [ 3 4 ] Erector spinae plane block (ESPB) is a recently described regional anaesthesia technique leading to multiple paravertebral blocks.…”
Section: Introductionmentioning
confidence: 99%